2008
DOI: 10.1289/ehp.10926
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution, Airway Inflammation, and Lung Function in a Cohort Study of Mexico City Schoolchildren

Abstract: BackgroundThe biological mechanisms involved in inflammatory response to air pollution are not clearly understood.ObjectiveIn this study we assessed the association of short-term air pollutant exposure with inflammatory markers and lung function.MethodsWe studied a cohort of 158 asthmatic and 50 nonasthmatic school-age children, followed an average of 22 weeks. We conducted spirometric tests, measurements of fractional exhaled nitric oxide (FeNO), interleukin-8 (IL-8) in nasal lavage, and pH of exhaled breath … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
160
2
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 202 publications
(177 citation statements)
references
References 52 publications
(64 reference statements)
9
160
2
6
Order By: Relevance
“…Similar inverse correlations between PM exposure and individual PEFR and FEV1 measurements have been reproduced internationally [60]. In the developing world, where indoor biomass burning can lead to PM levels exceeding 200 μg/m 3 , researchers demonstrated that chronic exposure in children can lead to adult COPD, increased rates of lung infection, and impaired lung function [61].…”
Section: Pm and Pulmonary Functionmentioning
confidence: 62%
“…Similar inverse correlations between PM exposure and individual PEFR and FEV1 measurements have been reproduced internationally [60]. In the developing world, where indoor biomass burning can lead to PM levels exceeding 200 μg/m 3 , researchers demonstrated that chronic exposure in children can lead to adult COPD, increased rates of lung infection, and impaired lung function [61].…”
Section: Pm and Pulmonary Functionmentioning
confidence: 62%
“…Airway inflammation has also been examined in a number of panel studies, using exhaled nitric oxide as a non-invasive measure of allergic inflammation. While there appears to be a clear relationship between ozone and health effects in children (Liu et al, 2009;Berhane et al, 2011;Nickmilder et al, 2007;Barraza-Villarreal et al, 2008;Sienra-Monge et al, 2004), the data for adults is mixed (Delfino et al, 2010b;Eiswerth, Douglass Shaw & Yen, 2005). There is little evidence from panel studies to demonstrate this association is stronger in asthmatic children (Berhane et al, 2011;BarrazaVillarreal et al, 2008).…”
Section: Experimental and Panel Studiesmentioning
confidence: 99%
“…Barraza-Villarreal et al (2008) show that the exposure to PM 2.5 provokes airway inflammation and decrement of lung function, and Holguin et al (2003) observed that the concentrations of PM 2.5 are related with cardiac dysfunction especially in elderly persons in MCMA.…”
Section: Toxic Effects and Human Health Riskmentioning
confidence: 99%